EFEK MEDIASI PERILAKU KEUANGAN PADA PENGARUH LITERASI KEUANGAN TERHADAP KEPUTUSAN INVESTASI BAGI PELAKU UMKM DI DAERAH ISTIMEWA YOGYAKARTA - Pratiwi, Puji; Atmoko, Alfriadi Dwi (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2023)
The purpose of this research aims to test empirically the mediating effect of financial behavior on the effect of financial literacy on investment decisions for MSMEs in DIY (Daerah Istimewa Yogyakarta). The method used in this research is quantitative. The population and sample of this study are MSME actors (Micro, Small and Medium Enterprises) in DIY. The sampling technique in this study was using an accidental sampling technique with a total sample of 188 respondents from MSME actors in DIY. The data source in this study is primary data using a questionnaire. The data analysis method in this study is path analysis using the Warp PLS application. The results of this study are that financial literacy can positively influence investment decisions for MSME actors in DIY, financial literacy can positively influence financial behavior for MSME actors in DIY, financial behavior can positively influence investment decisions for MSME actors in DIY. Financial behavior is able to mediate the effect of financial literacy on investment decisions for MSME actors in DIY.